2016
DOI: 10.1016/j.atherosclerosis.2016.06.030
|View full text |Cite
|
Sign up to set email alerts
|

The validity and reliability of continuous-wave near-infrared spectroscopy for the assessment of leg blood volume during an orthostatic challenge

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…For each time point (10 min, 90 min, 170 min, post-), data were averaged over 30 s and expressed relative to supine baseline. Our laboratory has previously reported that the Portalite device is able to monitor changes in tHb with acceptable validity and reliability (intraclass correlation, ICC, range: 0.75-0.98; Lucero et al, 2017;Stone, Fryer, Ryan, & Stoner, 2016) and changes in TSI with acceptable reliability (ICC: 0.7-0.9; Lucero et al, 2017).…”
Section: Calf Blood Volumementioning
confidence: 99%
“…For each time point (10 min, 90 min, 170 min, post-), data were averaged over 30 s and expressed relative to supine baseline. Our laboratory has previously reported that the Portalite device is able to monitor changes in tHb with acceptable validity and reliability (intraclass correlation, ICC, range: 0.75-0.98; Lucero et al, 2017;Stone, Fryer, Ryan, & Stoner, 2016) and changes in TSI with acceptable reliability (ICC: 0.7-0.9; Lucero et al, 2017).…”
Section: Calf Blood Volumementioning
confidence: 99%
“…4). [23][24][25][26] Many studies have investigated the use of NIRS to reveal the pathophysiology of patients with OI.27-31 NIRS offers an alternative solution for understanding the effects of a dysregulated autonomic nervous system on the delivery of blood to the brain. In addition, NIRS can potentially be used to monitor patients with inconclusive blood-pressure or heart-rate readings.…”
mentioning
confidence: 99%
“…4). [23][24][25][26] Many studies have investigated the use of NIRS to reveal the pathophysiology of patients with OI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings indicate that postural change might have a significant impact on the ability of XCEL to measure central and lower‐limb PWV accurately and precisely. During orthostasis there is a propensity for blood to pool in the subdiaphragmatic venous system (Stone, Fryer, Ryan, & Stoner, ). This is likely to have occurred in the present study, as indicated by the reduction in SV, CO and Pb (Stoner et al., ).…”
Section: Discussionmentioning
confidence: 99%